Pengaruh Kecerdasan Emosional dan Beban Kerja terhadap Kinerja Karyawan pada PT Pangan Sari Padjadjaran - Dewi Salmaningrum; Eman Sulaeman; Anwar Musadad (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to examine the influence of Emotional Intelligence and Workload on Employee Performance at PT Pangan Sari Padjadjaran using a quantitative research method. To investigate these effects, the study employed scale range analysis and SEM-PLS (Structural Equation Modeling – Partial Least Squares) analysis. The primary data source was a questionnaire distributed to all 105 employees of PT Pangan Sari Padjadjaran. The results indicate a partial relationship between Emotional Intelligence (X1) and Employee Performance (Y) of 31%, and a partial relationship between Workload (X2) and Employee Performance (Y) of 54.5%. These findings suggest that Emotional Intelligence and Workload are factors that can influence Employee Performance.